The Effect of English Listening and Speaking Application On Students’ Listening Skill at Lakidende University - Asri Nofa Rama; Dian Resty Pratiwi Ahmad; Nurwanti Nurwanti (Jurnal Pendidikan dan Konseling (JPDK), 2022)
English listening and speaking app is an English learning application that can be installed on students’ mobile phone. This study aimed to find out the effect of using English listening and speaking app on students’ listening skill and their perception. This study was experimental in nature thus there was an experimental group involved. There were 20 participants as the sample of this study. The qualitative data were calculated, and it was followed by analysing the qualitative instrument. Thus, this research used listening tests namely pre-test and post-test. The questionnaire consisted of three main questions asking about the students’ opinion. This study found that the students’ mean score improved significantly before and after the implementation of English listening and speaking app. There are two best features that best help the students in their listening activity namely vocabulary and pronunciation features. Besides, the students responded positively toward the use of this learning application on their listening skill improvement. This study suggests that the details of this finding need to be investigated further.